2014
DOI: 10.1002/pat.3261
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant polystyrene copolymers: preparation, thermal properties, and fire toxicities

Abstract: A new phosphorous-and nitrogen-containing reactive monomer, DMPMA, was first synthesized by nucleophilic substitution reaction of 2-(6-oxido-6H-dibenz[c,e][1,2]oxaphos-phorin-6-yl) methanol, N-hydroxymethyl acrylamide and methyldichlorophosphate. The copolymer of styrene (St) and DMPMA (poly(St-co-DMPMA)) was prepared and then characterized by Fourier transform infrared, differential scanning calorimetry, thermogravimetric analysis (TGA), microscale combustion calorimeter and steady-state tube furnace (SSTF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
(30 reference statements)
1
29
0
Order By: Relevance
“…Cerium-doped manganese oxide-graphene hybrid sheets were also found to suppress the amount of organic volatiles and CO during decomposition epoxy resins [99]. Less success was obtained on incorporating a new phosphorous-and nitrogen-containing reactive monomer to form a polystyrene copolymer [100]. The results obtained from the SSTF indicated that the carbon monoxide and smoke yield density were increased due to the incomplete combustion of the copolymer.…”
Section: Fire Retardantsmentioning
confidence: 70%
“…Cerium-doped manganese oxide-graphene hybrid sheets were also found to suppress the amount of organic volatiles and CO during decomposition epoxy resins [99]. Less success was obtained on incorporating a new phosphorous-and nitrogen-containing reactive monomer to form a polystyrene copolymer [100]. The results obtained from the SSTF indicated that the carbon monoxide and smoke yield density were increased due to the incomplete combustion of the copolymer.…”
Section: Fire Retardantsmentioning
confidence: 70%
“…Among different phosphorus-containing flame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) and its derivatives with a diphenyl structure have been used to reduce flammability of polymers such epoxy resin, polystyrene, polylactic acid, etc., owning to their high flame-retardant efficiency, water resistance, good oxidation and thermal stability. [15][16][17][18][19] However, to date, few people have studied the flame-retardant effect of DOPO and its derivatives in PMMA. [20] Inspired by the aforementioned concepts, herein, a novel DOPO-based monomer, DOPO-AA, is first prepared and then introduced into PMMA matrix via in situ copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…After adding GO-ODOPM, the T g of the composites decreased overall, but interestingly, as the amount of GO-ODOPM added increased, T g showed an upward trend. This may be due to the fact that when the addition amount of GO-ODOPM was low, the ODOPM group acts as a lubricant in the composite material, which increased the flexibility of the polystyrene chain, resulting in a decrease in the T g of the GO-ODOPM/PS composite microsphere [23]. With the increase of the addition amount of GO-ODOPM, GO sheets played a major role in the composite microspheres, which can inhibit the movement of PS molecular segments through interface interactions such as physical adsorption, and act as plasticizers, resulting in the increase of T g of GO-ODOPM/PS composite microspheres [24].…”
Section: Dsc Analysismentioning
confidence: 99%